The Relationship between Intellectual Capital, Financial Performance and financial literacy - Yusuf , Nurhaya; Pono, Maat; Reni, Andi; Aswan, Andi (International Journal of Accounting and Economics Studies, 2026)
Purpose: This article conceptualizes the relationship between intellectual capital and financial performance by proposing financial literacy as ‎a crucial mediating variable within the Small and Medium Enterprises (SMEs) context. Design/Methodology/Approach: This research em-‎ploys a systematic conceptual literature review grounded in the Resource-Based View (RBV) theory. The study synthesizes existing literature ‎to extend the dimensions of intellectual capital. Findings: While traditional RBV focuses on human and structural assets, this study introduces spiritual capital—encompassing religious values and ethics—as a vital third dimension of intellectual capital. The paper argues that indi-‎vidual capabilities and spiritual values are insufficient to maximize performance without financial literacy, which acts as a "translational ‎capability" to convert intangible knowledge into effective operational and investment decisions.
Keywords: Intelectual Capital; Financial Performace; Financial Literacy